2020
DOI: 10.1021/acs.jpcc.0c02453
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Singlet Self-Trapped Excitons in a New Family of White-Light-Emitting Zero-Dimensional Compounds

Abstract: As illumination is a fundamental human need, the exploration of illumination sources possessing high efficiency and broadband white-light emission is highly desirable. Zero-dimensional (0D) metal halide compounds are promising candidates, and some lead-free antimony-containing compounds exhibit bimodal white-light emissions. However, their origins are still unclear. To solve this issue, we designed and prepared a new family of 0D metal halide compounds consisting of [M(18-crown-6)] + (M = NH 4 , Rb) and SbX 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…3b). 42–44 To reveal the photophysical process, time-resolved PL spectrum monitoring at 610 nm was performed and fitted by a biexponential function giving an average lifetime of 5.078 μs and 5.978 μs at 300 K and 80 K, respectively (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…3b). 42–44 To reveal the photophysical process, time-resolved PL spectrum monitoring at 610 nm was performed and fitted by a biexponential function giving an average lifetime of 5.078 μs and 5.978 μs at 300 K and 80 K, respectively (Fig. 3c).…”
Section: Resultsmentioning
confidence: 99%
“…The Sb–Br bond lengths range from 2.5174(8) to 2.7770(5) Å and 2.5196(7) to 2.7754(5) Å for 1·EtOH-Br and 1·MeCN-Br , respectively (Table S2†), comparable with those of previously reported 0D antimony( iii ) bromides. 26,28,30,31,51…”
Section: Resultsmentioning
confidence: 99%
“…Analogous to Bi-based perovskites, the trivalent Sb is isoelectronic with divalent Pb cations and possesses similar electronegativity. [64][65][66][67][68][69][70] Therefore, Sb-based halide perovskites are a potential alternative to Pb-based perovskites for light-emitting applications to address the toxicity and environmental stability issues. [71,72] For instance, two organic-inorganic Sb-based halides with specific forms of (TTA) 2 SbCl 5 (TTA = tetraethylammonium) and [53] Copyright 2017, Wiley-VCH.…”
Section: Sb-based Perovskites For Phosphor-converting Wledsmentioning
confidence: 99%
“…Similarly, Xu et al reported an intense white-light emission with CIE coordinates of (0.43, 0.34) from organic-inorganic hybrid (C 12 H 24 O 6 ) 2 SbCl 5 powders. [67] Considering the volatile nature of organic chains under harsh conditions, more attempts have been implemented to use inorganic cations to realize more stable materials. [68] Zhang et al reported for the first time the synthesis and optical properties of all-inorganic Cs 3 Sb 2 X 9 QDs (X = Cl, Br, I) by a modified ligand-assisted reprecipitation strategy.…”
Section: Sb-based Perovskites For Phosphor-converting Wledsmentioning
confidence: 99%